Le blog intime au croisement des genres de l’écriture de soi - Oriane Deseilligny (Itinéraires, 2010)
If we consider the use of the Internet and the practice of writing, weblogs have followed personal websites. In this paper, we examine the way by wich those electronic writing practices have inherited some discursive and morphological forms from classical genres, namely diaries and correspondence. Diary and intimate correspondence are two genres of self-writing, the evolutions of which are linked. Thus, weblogs are in line with the concept of self-writing defined by Michel Foucault.